Characterization of the Cancer-Associated Meprin Βeta Variants G45R and G89R - Gellrich, Antonin; Scharfenberg, Franka; Peters, Florian; Sammel, Martin; Helm, Ole; Armbrust, Fred; Schmidt, Frederike; Lokau, Juliane; Garbers, Christoph; Sebens, Susanne; Arnold, Philipp; Becker-Pauly, Christoph (Frontiers in Molecular Biosciences, 2021)
Meprin β is a metalloprotease associated with neurodegeneration, inflammation, extracellular matrix homeostasis, transendothelial cell migration, and cancer. In this study, we investigated two melanoma-associated variants of meprin β both exhibiting a single amino acid exchange, namely meprin β G45R and G89R. Based on structural data of meprin β and with regard to the position of the amino acid exchanges, we hypothesized an increase of proteolytic activity in the case of the G45R variant due to the induction of a potential new activation site, and a decrease of proteolytic activity from the G89R variant due to structural instability. Indeed, the G89R variant showed overall a reduced expression level compared to wild-type meprin β, accompanied by decreased activity, lower cell surface expression but strong accumulation in the endoplasmic reticulum. This was further supported by the analysis of the shedding of the interleukin-6 receptor (IL-6R) by meprin β and its variants. In transfected HEK cells, the G89R variant was found to generate less soluble IL-6R, whereas expression of meprin β G45R resulted in increased shedding of the IL-6R compared to wild-type meprin β and the G89R variant. A similar tendency of induced shedding capacity of G45R was seen for the well-described meprin β substrate CD99. Furthermore, employing an assay for cell migration in a collagen IV matrix, we observed that transfection of wild-type meprin β and the G45R variant resulted in increased migration of HeLa cells while the G89R variant led to diminished mobility.